Case Report: Transvertebral transposition of the spinal cord for recovery after paraplegia during kyphoscoliosis surgery - Chen, Chao; Zhao, Zhen; Li, Jing; Xu, Qiankun; Zhong, Weibin; Wang, Bingjin; Zhu, Lingwei; Yang, Cao; Gao, Yong (Frontiers in Neurology, 2022)
Introduction Neurological impairment during spinal deformity surgery is the most serious possible complication. When confronting intraoperative neurophysiological monitoring alerts, various surgical management methods such as the release of implants and decompression of the spinal cord are always performed. Transvertebral transposition of the spinal cord is rarely performed, and its role in the management of acute paraplegia is seldom reported. Case description The authors present two patients with kyphoscoliosis who experienced neurological deficits and abnormal neurological monitoring intraoperatively or post-operatively that were detected during correction surgery. Acute paraplegia was confirmed by a wake-up test. Subsequent spinal cord transposition was performed. Intraoperative neurophysiological monitoring motor-evoked potentials (MEPs) and somatosensory-evoked potentials (SEPs) were performed to detect the changes during the process. After transvertebral transposition of the spinal cord, the MEPs and SEPs were significantly improved in both patients during surgery. The spinal cord function was restored post-operatively and recovered to normal at the final follow-up in two patients. Conclusion This case demonstrated that instead of decreasing the correction ratio of kyphoscoliosis, transvertebral transposition of the spinal cord under intraoperative neurophysiological monitoring may be an alternative therapeutic strategy for acute spinal cord dysfunction caused by deformity correction surgeries.